Students Motivation and Parental Support on Modular Learning - B ABELLANEDA Ed.D., JUDITH; B CATACUTAN, AILEEN; C MONEVA, JERALD; VILLAMOR, BRIDGET (International Research in Education, 2022)
The goal of the study was to look over the association between students' level of motivation and the parental support of the parents. Respondents in this study included 180 students from various Mandaue, City schools. The Students Motivation and Parental Support Assessment (SMPSA) questionnaire was used as an assessment tool to gather data. The data was analyzed and using weighted mean and chi- square. The findings revealed an association between the level of student motivation and parental support among students. Those students who are motivated had possibility to achieve their dreams and goals in life and to the parents who are always supported to their children and guide them to have better pathways in the future.